2014
DOI: 10.4056/sigs.5088950
|View full text |Cite
|
Sign up to set email alerts
|

High quality draft genome sequence of Olivibacter sitiensis type strain (AW-6T), a diphenol degrader with genes involved in the catechol pathway

Abstract: Olivibacter sitiensis Ntougias et al. 2007 is a member of the family Sphingobacteriaceae, phylum Bacteroidetes. Members of the genus Olivibacter are phylogenetically diverse and of significant interest. They occur in diverse habitats, such as rhizosphere and contaminated soils, viscous wastes, composts, biofilter clean-up facilities on contaminated sites and cave environments, and they are involved in the degradation of complex and toxic compounds. Here we describe the features of O. sitiensis AW-6T, together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Whitehead [ 99 ] emphasized that Prevotella species in the rumen could contribute to cell wall degradation through synergistic interactions with various species of cellulolytic bacteria. Moreover, the research of Ntougias et al [ 100 ] revealed that Olivibacter sitiensis is a xylanolytic bacterium which is involved in the cleavage of β -1,4-xylosic bonds in hemicelluloses. This statement supported the abundance of O. sitiensis in the present study, which is also observed during a high-forage diet condition.…”
Section: Discussionmentioning
confidence: 99%
“…Whitehead [ 99 ] emphasized that Prevotella species in the rumen could contribute to cell wall degradation through synergistic interactions with various species of cellulolytic bacteria. Moreover, the research of Ntougias et al [ 100 ] revealed that Olivibacter sitiensis is a xylanolytic bacterium which is involved in the cleavage of β -1,4-xylosic bonds in hemicelluloses. This statement supported the abundance of O. sitiensis in the present study, which is also observed during a high-forage diet condition.…”
Section: Discussionmentioning
confidence: 99%
“…This enrichment was reflected by the dominant family Sphingobacteriaceae, especially of the abundant OTU AB267714.1.1482 belonging to the genus Olivibacter. Strains belonging to this genus have been found to be involved in the degradation of phenanthrene (Villaverde et al, 2019) or diphenol (Ntougias et al, 2014). On the other hand, treatment with TCS caused a decline in members of the class Cytophagia at and days by 3.4% and 3.9% respectively, but then increased by 6.5% at day 50 (Fig.…”
Section: Impact Of Ppcps On the Composition Of The Bacterial Communitiesmentioning
confidence: 97%
“…was identified and characterized for first time during the process of production of olive oil (Ntougias et al, 2007). Different species of the genus Olivibacter can be found in contaminated soils, wastes and cave environments, which can be able to degrade complex and toxic chemicals (Ntougias et al, 2015). Szabó et al (2011) isolated a novel strain capable of degrading hydrocarbons, Olivibacter oleidegradans , from a clean-up facility (biofilter) in a hydrocarbon contaminated site.…”
Section: Resultsmentioning
confidence: 99%